Kajian Gender Dalam Pendidikan Islam dan Transformasi Pendidikan Berkeadilan Gender - Nuridin Nuridin (Peneliti.net, 2023)
This research used the library research method or library, in which the method of collecting data on gender studies was through reference books, notes, articles and various other journals to obtain research results. Discrimination that occurs in the world of education is currently quite widespread. Discrimination results in losses for one of the parties who are cornered. The gap in educational participation between men and women is one of the aspects that must be considered in fair gender equality. There are several factors that influence the occurrence of inequality or injustice, namely structural and cultural factors. In addition to development policies that are not gender sensitive, the community still carries out cultural practices that are gender biased. Facing conditions like this, of course, real efforts are needed to empower women with education that is more gender-equitable. This study aims to reveal gender differences in equitable Islamic education.